TRACING THE HISTORICAL EVOLUTION AND ESTABLISHMENT OF FAMILY COURTS IN INDIA: AN ANALYSIS OF THEIR ORIGINS AND SIGNIFICANCE - Singh, Bandana; Mishra, Prakash Chandra (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The establishment of family courts in India has been a significant development in the Indian judicial system. Family courts are dedicated to resolving disputes related to family and domestic matters, and their establishment has been a significant step towards providing timely and effective resolution of such disputes. The first family court was established in Chennai in 1976, and since then, several family courts have been established in different states across India. The purpose of present paper is to provide a comprehensive understanding of the reasons why family courts were established in India, the challenges faced during their establishment, and their impact on the Indian judicial system.